Intellectual Capital and Firm Performance: The Mediating Role of Governance - Pipit Rengganis; Estu Widarwati; Nunik Nurmalasari; Mutqi Sopiawadi (Proceeding of National Conference on Accounting & Finance, 2023)
Intellectual capital is an intangible asset, resource, science and technology and knowledge owned by a company that distinguishes it from other companies. Intellectual capital has developed and has become a very important capital and is a critical part for companies to gain competitive advantage in facing economic developments where competition is getting stronger. This study aims to examine the effect of intellectual capital on financial performance with corporate governance as a moderating variable in companies on the Indonesia Stock Exchange. Intellectual capital is proxied by value added intellectual coefficient (VAICTM), financial performance measured by return on equity (ROE), then corporate governance proxied by independent commissioners and audit committees. The sample are 33 companies all sectors listed on Indonesia Stock Exchange (IDX) from 2015 to 2021 and the datas analyzed using panel data regression and moderating regression analysis (MRA). The results show that the intellectual capital variable on financial performance has significant positive effect. We find that the audit committee as a moderating variable can significantly strengthen the relationship between intellectual capital and financial performance, but there is no strong evidence independent commissioners has significant moderating role. However, Companies that are able to manage intellectual capital and implement good corporate governance will achieve competitive advantage in improving the company's financial performance.